Prototype IOT-based Soil PH Measurement Tool with Esp8266 at UPT Palawija Tanjung Selamat - Putri, Raissa Amanda; Fadillah, Muhammad Taufik; Prayuda, Wahyu Putra; Wibowo, Muhammad Rizky (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2024)
The goal of this research is to build and create a prototype tool capable of monitoring soil pH automatically by employing Internet of Things (IoT) technology using NodeMCU ESP8266 at UPT Palawija Tanjung Selamat. The challenge is in the limited time and effort required for manual soil pH measurement, which can impede the process of routinely checking soil quality. The technique uses a pH sensor coupled with a NodeMCU ESP8266 to wirelessly send data to an Internet of Things platform. The instrument will be built to be able to provide data in real time to the monitoring system and measure the pH of the soil on a regular basis. To guarantee the precision of the test results in this instance, the pH sensor will be meticulously calibrated. The ultimate product of this prototype design is anticipated to be a device that can continuously monitor the pH of soil without requiring direct input from land managers or farmers. It is anticipated that this instrument would offer precise and trustworthy data regarding the degree of soil acidity at the site under remote observation. Therefore, it is anticipated to improve soil management's efficacy and efficiency and allow for prompt remedial action in the event that data collection warrants it.